Pengaruh Media Pembelajaran Pop Up Book terhadap Hasil Belajar Peserta Didik Materi Sistem Ekskresi Manusia - Suherman, Wahdania; Rapi, Muh.; Hasanah, Ummul (Al-AHYA: Jurnal Pendidikan Biologi, 2023)
This research aims: 1) to find out the learning outcomes of students on the material of the human excretory system that is taught using pop-up book media; 2) to find out the learning outcomes of students on the material of the human excretory system without using textbook media; and 3) to find out the effect of pop-up book media on students learning outcomes on the material of the human excretory system. This type of research was quasi-experimental with a non-equivalent control group design. Sampling used a purposive sampling technique. The samples in this research are class VIII C (experimental) and class VIII D (control) of class VIII MTs. Madani Alauddin Pao-pao . The data were analyzed in descriptive and inferential statistics. The average posttest learning outcome of students taught using pop-up books was 81.25 (high). The average posttest learning outcomes of students taught using textbooks were 65.54 (medium). The t-test significance value is sign α = 0.000 ˂ 0,05, so it implies a significant influence between the use of pop-up book media on students' learning outcomes in the material of the human excretory system class VIII MTs. Madani Alauddin Pao-pao.